Um modelo de sistema de gerenciamento da informação para transferência tecnológica no âmbito da cooperação universidade - empresa - Strauhs, Faimara do Rocio (1998)
The objective of this research is the proposal of a model of an Information Management System for Technology Transfer to be used in Education, Research and Development Institutions. The proposed model aims at flexibility and generality, só that it can be adapted to many kinks of organizations that generate high-value information. This model was based on models available in the literature and on the direct and systematic observation of DISQUE-CEFET, an embryonic Information Management System. DISQUE-CEFET was developed and is used by CEFET-PR (Centro Federal de Educação Tecnológica do Paraná), a federal educational institution with research and development activities that is well known nationally among other institutions for its pioneering and effective methods of community interaction, particularly with the productive sector. The theoretical basis presents the current historical-technological paradigm change as the Industrial Society is transformed into the Information Society. Information, the main technological input of this era, is characterized in relation with its generation process, processing and diffusion, and the interference of natural barriers. The evolution in information processing resulted in Information Systems and in theirs specialized forms as Information Management Systems. A generic model is proposed, which is based on literature research and on data collected from DISQUE-CEFET. The proposed model includes all the phases of strategic and operational planning. The main contribution of this research is not the model itself but in its systematic planning, developed from the comparison of theoretical models and from documented data about the planning and implantation of DISQUE-CEFET. Another contribution is the identification of new research themes, including the implementation of the proposed model, allowing its validation, correction and evolution. Improvements in the model include the new forms of information diffusion, particularly Technological Information. This Information is generated in Education, Research and Development Institutions, and is often not available to the productive sector, but provides leverage to the development of the Information Society.